2011
DOI: 10.1159/000329851
|View full text |Cite
|
Sign up to set email alerts
|

Evo-Devo and Brain Scaling: Candidate Developmental Mechanisms for Variation and Constancy in Vertebrate Brain Evolution

Abstract: Biologists have long been interested in both the regularities and the deviations in the relationship between brain, development, ecology, and behavior between taxa. We first examine some basic information about the observed ranges of fundamental changes in developmental parameters (i.e. neurogenesis timing, cell cycle rates, and gene expression patterns) between taxa. Next, we review what is known about the relative importance of different kinds of developmental mechanisms in producing brain change, focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 180 publications
4
59
0
1
Order By: Relevance
“…Variation in the timing of neurogenesis, cell-cycle rates and patterning of progenitor pools suggest these processes can, at least in part, evolve independently [104], offering alternative routes through which selection can act. These three routes to the diversification of brain structure may take effect at different stages of development.…”
Section: (E) Developmental Models Of Mosaic Evolutionmentioning
confidence: 99%
“…Variation in the timing of neurogenesis, cell-cycle rates and patterning of progenitor pools suggest these processes can, at least in part, evolve independently [104], offering alternative routes through which selection can act. These three routes to the diversification of brain structure may take effect at different stages of development.…”
Section: (E) Developmental Models Of Mosaic Evolutionmentioning
confidence: 99%
“…In mammals, the volumes of the major brain subdivisions appear to be evolving primarily in concert [Finlay and Darlington, 1995;Whiting and Barton, 2003;Striedter, 2005] whereas in birds, the major brain subdivisions seem to be evolving as a mosaic [Boire and Baron, 1994;Iwaniuk et al, 2004]. However, all groups show evidence of both processes, since there is also evidence for mosaic brain evolution in mammals [Barton and Harvey, 2000;Brown, 2001;Dobson and Sherwood, 2011;Hager et al, 2012] and concerted brain evolution in birds [Charvet et al, 2011;Guti茅r-rez-Ib谩帽ez et al, 2014]. This dichotomy also exists between the major clades of fishes, with cartilaginous fishes primarily showing a concerted pattern of brain evolution [Yopak et al, 2010] whereas bony fishes seem to primarily exhibit a mosaic pattern [Kotrschal et al, 1998;Gonzalez-Voyer et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in evolutionary developmental neurobiology has shown that these evolutionary increases in brain region volumes are often caused by delays in cell cycle exit of neuronal precursors (5,6). Among birds, for example, parrots and songbirds exhibit delayed telencephalic neurogenesis relative to chicken-like birds (7)(8)(9).…”
mentioning
confidence: 99%